DETERMINATION OF THE PLATINUM-GROUP ELEMENTS IN GEOLOGICAL MATERIALS BY ICP-MS USING MICROWAVE DIGESTION, ALKALI FUSION AND CATION-EXCHANGE CHROMATOGRAPHY - Jarvis I.; Totland M.M.; Jarvis K.E. (My University, 1997)
A new method for determination of the platinum group elements (PGE's: Ru; Rh; Pd; Ir; Pt) in geological samples, using microwave-assisted acid digestion and alkali fusion, separation of the PGE's by cation-exchange chromatography, and analysis by inductively coupled plasma-mass spectrometry (ICP-MS) is described. Experiments using synthetic multi-element solutions have been used to establish: conditions for cleaning and conditioning AG 50W-X8 cation-exchange resin; solution requirements for loading samples onto the resin; optimum column size and elution parameters. Recovery studies show no significant retention of Ru, Rh, Pd, Ir and Pt on the resin, at levels ranging from 0.1 μg to 500 μg. Recovery of Au is only complete for solutions containing > 1 μg. Our optimised cation-exchange procedure has been evaluated using 1 g sub-samples of eight reference materials (RM's: DZE-1; DZE-2; MA-2a; PTA-1; PTC-1; PTM-1; SARM7; SU-la), digested using microwave heating in sealed vessels with aqua regia-HF, followed by alkali fusion of insoluble residues, evaporation of solutions to near dryness, and dissolution in 0.5 M HCl. Matrix elements were removed from sample solutions by cation-exchange chromatography on AG 50W-X8, prior to analysis by ICP-MS. Lower limits of quantitative analysis for 1-g sub-samples range from 1.3 ng g-1 for Rh to 11 ng g-1 for Pd, two orders of magnitude better than those achieved for unseparated samples. Good agreement with reference values has been obtained for Ru, Rh, Pd and Ir in most RM's, but Pt results were generally low. Gold is lost on the ion-exchange resin. Preliminary work indicates that, with minor modification, our method may be applied successfully to larger (5 g) sample sizes, and offers an alternative to fire assay for the determination of Ru, Rh, Pd and Ir.
Keywords: PLATINUM GROUP ELEMENTS; PRECIOUS METALS; RU, RH, PD, IR DETERMINATION; GEOLOGICAL SAMPLES; MICROWAVE DIGESTION; ALKALI FUSION; CATION EXCHANGE CHROMATOGRAPHY; INDUCTIVELY COUPLED PLASMA-MASS SPECTROMETRY